2012
DOI: 10.1016/j.ijmedinf.2011.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Results of a randomized controlled trial to assess the effects of a mobile SMS-based intervention on treatment adherence in HIV/AIDS-infected Brazilian women and impressions and satisfaction with respect to incoming messages

Abstract: Objective To assess whether a warning system based on mobile SMS messages increases the adherence of HIV-infected Brazilian women to antiretroviral drug-based treatment regimens and their impressions and satisfaction with respect to incoming messages. Design A randomized controlled trial was conducted from May 2009 to April 2010 with HIV-infected Brazilian women. All participants (n = 21) had a monthly multidisciplinary attendance; each participant was followed over a 4-month period, when adherence measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
219
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(224 citation statements)
references
References 21 publications
3
219
0
2
Order By: Relevance
“…13 Several studies have demonstrated the practicality of CPBMI use in various aspects of HIV treatment. [44][45][46] As a consequence, many investigators have attempted to develop management systems for better outcomes of HIV patients, and scientific evidence of the clinical effects of mobile applications has been reported.…”
Section: Health Management Systems Using Cellular Phonesmentioning
confidence: 99%
“…13 Several studies have demonstrated the practicality of CPBMI use in various aspects of HIV treatment. [44][45][46] As a consequence, many investigators have attempted to develop management systems for better outcomes of HIV patients, and scientific evidence of the clinical effects of mobile applications has been reported.…”
Section: Health Management Systems Using Cellular Phonesmentioning
confidence: 99%
“…Other interventions using cognition as a change mechanism focused on both ART adherence and virologic suppression (k = 4); one study [19] focused on both ART adherence and care retention, and one study focused on both care retention and virologic suppression [22]. All of the eHealth interventions using cognition were augmented with another change mechanism except for two studies [i.e., [43, 44] ]. About two-thirds (k = 13) of the studies using cognition showed either preliminary or proven evidence of efficacy for improving HIV medication adherence.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, in a pre-rollout qualitative acceptability study of WelTel Retain, both HIV-infected individuals and clinicians felt that the SMS intervention would improve communication and lead to early identification of clinical problems, resulting in improved retention [40]. In a small study of SMS reminders to improve adherence among Brazilian women, most participants reported that SMS helped them adhere; one participant noted that the messaging system Bhelps me not to give up [ 41]. Likewise, a focus group-based study in Uganda among HIV-positive youth participants reported that an SMS-based adherence reminder system would help them to adhere [42].…”
Section: Uptake/acceptabilitymentioning
confidence: 99%